Implementasi Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit 4.1 Pada Bidang Penyelenggaraan E-Government Dinas Komunikasi dan Informatika Kota Kediri - Mia Sahdana; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Department of Communication and Information Kediri (Diskominfo) is a government institution authorized in the field of ICT management had problems in the delivery and support of information technology services, contained in the field of E-Government Organization. Hence, IT governance evaluation is required using the COBIT 4.1 framework on Deliver and Support (DS) domains, especially the problems found in DS1 defined and managed service levels, DS5 ensured system security, DS7 educated and train users and DS10 managed problems. The purpose of this research was aimed to know the state of existing IT governance by defined RACI Chart, calculated maturity level and gave recommendation in the form of document design such as procedure manual, work instruction, form and report to achieve the expected state of IT governance. The data itself was collected with several methods such us the assessment sheets, interviews and observations. From the maturity level calculation results obtained average results on DS1, DS5, DS7 and DS10 of 2.00 and gap analysis of 1.00. In order to achieve the maturity level 3.00, the recommendation was made with Standard Operating Procedure (SOP) in every existing IT process and completed documentation of standard format which will be implemented by field of E-Government Organization, so that management of IT services can be stable and controlled.